Quantum cryptography: a view from classical cryptography. (25th May 2017) - Buchmann, Johannes; Braun, Johannes; Demirel, Denise; Geihs, Matthias
Abstract: Much of digital data requires long-term protection of confidentiality, for example, medical health records. Cryptography provides such protection. However, currently used cryptographic techniques such as Diffe-Hellman key exchange may not provide long-term security. Such techniques rely on certain computational assumptions, such as the hardness of the discrete logarithm problem that may turn out to be incorrect. On the other hand, quantum cryptography—in particular quantum random number generation and quantum key distribution—offers information theoretic protection. In this paper, we explore the challenge of providing long-term confidentiality and we argue that a combination of quantum cryptography and classical cryptography can provide such protection.